Quantum-Size FeS2 with Delocalized Electronic Regions Enable High-Performance Sodium-Ion Batteries Across Wide Temperatures - Tianlin Li; Danyang Zhao; Meiyu Shi; Chao Tian; Jie Yi; Qing Yin; Yongzhi Li; Bin Xiao; Jiqiu Qi; Peng Cao; Yanwei Sui (Nano-Micro Letters)
Highlights Quantum-scaled FeS2 induces delocalized electronic regions, effectively reducing electrostatic potential barriers and accelerating Na+ diffusion kinetics. The free charge accumulation regions were formed by edge mismatched atoms, activating numerous electrochemically sites to enable high-capacity Na+ storage and ultrafast-ion transport across wide temperature range (−35 to 65 °C). The FeS2 QD/MXene anode delivers superior wide-temperature capacity of 255.2 mAh g−1 (−35 °C) and 424.9 mAh g−1 (65 °C) at 0.1 A g−1. The FeS2 QD/MXene//NVP cell achieves a record energy density of 162.4 Wh kg⁻1 at − 35 °C.